INTEGRATED MARKETING ANALYSIS ON BRAND UNDERSTANDING AND ITS IMPACT ON CUSTOMER LOYALTY OF MICRO, SMALL AND MEDIUM ENTERPRISES IN THE FASHION SECTOR IN MAKASSAR CITY - azwar ramadhana anasrullah (Scientium Management Review, 2023)
The research objective is to analyze integrated marketing on brand understanding and its impact on brand understanding and customer loyalty. The research approach used is a quantitative approach. The location of this research is the MSME SMEs in the fashion sector in Makassar City. The sample size is 132 MSME actors. The collection technique uses simple random sampling. The data collection method used is a questionnaire. The analytical method used is path analysis and the Sobel test. The results of the study prove that: 1. Integrated marketing has a positive and significant effect on customer loyalty. 2. Integrated marketing has a positive and significant effect on brand understanding. 3. Brand understanding has a positive and significant effect on customer loyalty.